A cytomegalovirus DNA vaccine induces antibodies that block viral entry into fibroblasts and epithelial cells. Issue 51 (16th December 2015) - McVoy, Michael A.; Lee, Ronzo; Saccoccio, Frances M.; Hartikka, Jukka; Smith, Larry R.; Mahajan, Rohit; Wang, Jian Ben; Cui, Xiaohong; Adler, Stuart P.
Abstract: A vaccine to prevent congenital cytomegalovirus (CMV) infections is a national priority. Investigational vaccines have targeted the viral glycoprotein B (gB) as an inducer of neutralizing antibodies and phosphoprotein 65 (pp65) as an inducer of cytotoxic T cells. Antibodies to gB neutralize CMV entry into all cell types but their potency is low compared to antibodies that block epithelial cell entry through targeting the pentameric complex (gH/gL/UL128/UL130/UL131). Hence, more potent overall neutralizing responses may result from a vaccine that combines gB with pentameric complex-derived antigens. To assess the ability of pentameric complex subunits to generate epithelial entry neutralizing antibodies, DNA vaccines encoding UL128, UL130, and/or UL131 were formulated with Vaxfectin ®, an adjuvant that enhances antibody responses to DNA vaccines. Mice were immunized with individual DNA vaccines or with pair-wise or trivalent combinations. Only the UL130 vaccine induced epithelial entry neutralizing antibodies and no synergy was observed from bi- or trivalent combinations. In rabbits the UL130 vaccine again induced epithelial entry neutralizing antibodies while UL128 or UL131 vaccines did not. To evaluate compatibility of the UL130 vaccine with DNA vaccines encoding gB or pp65, mono-, bi-, or trivalent combinations were evaluated. Fibroblast and epithelial entry neutralizing titers did not differ between rabbits immunized with gB alone vs. gB/UL130, gB/pp65, or gB/UL130/pp65 combinations, indicating a lack of antagonism from coadministration of DNA vaccines. Importantly, gB-induced epithelial entry neutralizing titers were substantially higher than activities induced by UL130, and both fibroblast and epithelial entry neutralizing titers induced by gB alone as well as gB/pp65 or gB/UL130/pp65 combinations were comparable to those observed in sera from humans with naturally-acquired CMV infections. These findings support further development of Vaxfectin ® -formulated gB-expressing DNA vaccine for prevention of congenital CMV infections.